Industrial Policy Effects and the Case for Competition - Pop, Georgiana; Connon, Davida (World Bank, Washington, DC, 2020)
It is conventional wisdom that industrial policies can be at odds with competitive markets. This note examines the historical basis for industrial policy and empirical effects. Although the direct effects of industrial policy are mixed, the indirect effects often involve market distortions. By contrast, the literature is broadly united on the benefits of competition for productivity and innovation. This review finds that the most successful industrial policies reinforce competition, suggesting that competition policy and certain types of industrial policy can be crafted as complements.